5b-48+2b=b+49

Simple and best practice solution for 5b-48+2b=b+49 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5b-48+2b=b+49 equation:


Simplifying
5b + -48 + 2b = b + 49

Reorder the terms:
-48 + 5b + 2b = b + 49

Combine like terms: 5b + 2b = 7b
-48 + 7b = b + 49

Reorder the terms:
-48 + 7b = 49 + b

Solving
-48 + 7b = 49 + b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-1b' to each side of the equation.
-48 + 7b + -1b = 49 + b + -1b

Combine like terms: 7b + -1b = 6b
-48 + 6b = 49 + b + -1b

Combine like terms: b + -1b = 0
-48 + 6b = 49 + 0
-48 + 6b = 49

Add '48' to each side of the equation.
-48 + 48 + 6b = 49 + 48

Combine like terms: -48 + 48 = 0
0 + 6b = 49 + 48
6b = 49 + 48

Combine like terms: 49 + 48 = 97
6b = 97

Divide each side by '6'.
b = 16.16666667

Simplifying
b = 16.16666667

See similar equations:

| 7xc=798 | | n^2+2=1 | | 1/2(18)(10) | | Lnx=x+5 | | -2m-2n=56 | | -6+3x+3=6x+3-3x | | 32+(3x+8)+(180-5x)=180 | | 8xc=896 | | 34=16+b+14 | | 7/6-8= | | q-49+q=q+50 | | -4+-1=24 | | 2x+88=2(2x+16) | | -(x-8)+4=2(6)+x | | b-44+b=b+42 | | -(x-8)+4=2(-6)+x | | 0.9*0.85= | | 146+2h=974 | | u-21+u-21=u+19 | | (0.3x+1234)*0.6-321+45x-6=9999 | | 668=4(x+16) | | q+39+44=5q+42 | | 8-5(x-3)=6-4(x+2) | | 7s+33=14s-48 | | 4x=34+8 | | y=2/7x-1 | | 3x-19+31=x+47 | | 0.7z+7=8.1z-19.4 | | -(x-8)+4=2(-10)+x | | H(t)=20t-4.9t^2+2 | | a+32+45=15a-44 | | 9x-45=4x+24 |

Equations solver categories